The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1021/np0005558
|View full text |Cite
|
Sign up to set email alerts
|

Norditerpenoid and Diterpenoid Alkaloids from Turkish Consolida orientalis

Abstract: From the aerial parts of Consolida orientalis collected in Turkey, a new diterpenoid alkaloid designated as consorientaline has been isolated along with the known norditerpenoid alkaloids delsoline, delcosine, gigactonine, and takaosamine. The structure of consorientaline (1) was established by spectroscopic studies and chemical correlation with dihydroajaconine (2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 12 publications
1
7
0
1
Order By: Relevance
“…This was consistent with the presence of an N-CH 2 -CHO group [4,5]. Through-space 1 H-13 C coupling of the resonance for the tertiary methyl protons at 0.96 (3H, s) and resonances for atoms at 32.7 (C-4), 40.0 (C-3), 43.9 (C-5), and 58.1 (C-20) confirmed that an 18-methyl was present.…”
supporting
confidence: 77%
“…This was consistent with the presence of an N-CH 2 -CHO group [4,5]. Through-space 1 H-13 C coupling of the resonance for the tertiary methyl protons at 0.96 (3H, s) and resonances for atoms at 32.7 (C-4), 40.0 (C-3), 43.9 (C-5), and 58.1 (C-20) confirmed that an 18-methyl was present.…”
supporting
confidence: 77%
“…H-15b H-16, OCH 3 -14 C-7, C-16 C5, and consorientealine (Desai et al, 1993;Meriçli F. et al, 2001). Except for the aldehyde group, there were six O-bearing C atoms present as shown by the signals at δ C 87.…”
Section: Resultsmentioning
confidence: 99%
“…Delphinium anthriscifolium Hance is composed of alkaloids, fixed oils, lipoids, and glycosides. Delsoline and eldeline are the two main alkaloids of D. anthriscifolium Hance [ 3 5 ]. Delsoline has a curare-like effect and a ganglion-blocking effect and can be used to relieve muscle tension or hyperkinesia.…”
Section: Introductionmentioning
confidence: 99%